Environmental considerations within manufacturing strategy - Crowe, Déirdre (Trinity College (Dublin, Ireland). Trinity Business School, 2008)
This thesis examines innovative entrepreneurial firms and their engagement in environmental management in the context of sustainable development. The interrelationships of environmental management with innovation and other strategic processes are studied in order to gain insights on current necessary resources, capabilities and motivations and to inform future orientation of firms towards sustainable development. The thesis begins with a discussion on sustainable development and the role of innovation. Environmental management in organisations is embedded in the concept of sustainable development. The central role played by organisations in sustainable development as well as in innovation is discussed. Approaches to study sustainable development include: ecological modernisation theory, industrial ecology, the systems approach and the role of innovation. These approaches are discussed. The role of innovation in reaching sustainable development is highlighted and, drawing on the literature on innovation and competitiveness, it suggests a possible framework to link societal and organisational level goals for sustainable development. The focus of this research is at the level of the organisation/firm and the literature review discusses some theoretical perspectives from the organisation and strategic management literatures. These include institutional and strategic perspectives that provide a theoretical foundation for the research and analysis: institutional theory, stakeholder theory, contingency theory and the resource-based view. The combination of institutional and strategic perspectives provides a comprehensive framework which is compatible with the use of the innovation capability perspective and the production capability triad and the entrepreneurial firm. This is a mixed-methods study and two sources of data are employed: international survey and case study. The first phase of this research, which employs data from the International Manufacturing Strategy Survey (IMSS), takes a resource-based view. The IMSS survey comprised 558 respondents from 17 countries. Innovation and performance related variables were identified and examined in conjunction with environmental considerations in manufacturing strategy. The IMSS survey comprised 558 respondents from 17 countries. Innovation and performance related variables were identified based on the literature. A measure of the salience of the environment in manufacturing strategy was determined - the environment in strategy (ES) index. This was developed using the relative position of the environmental item within four key manufacturing strategy questions. Negative, neutral and positive ES groups are identified. There are some significant relationships between the ES index and the innovation and performance variables. However, regression models identify only three variables predicting the ES index: R&D, influence of manufacturing on business/marketing strategies and ISO14001. The results also indicate that these are weak and account for small variances in the ES index meaning the innovation and performance variables have poor predictive capacity. The results of the comparative analyses indicate the same significant variables and they give a better picture of the relationships with the ES index. However, links between the ES index and the innovation and performance variables remain inconclusive. Following this analysis four firms were selected for case study accompanied by two others recommended by experts in the field of environmental management. These six cases are then analysed individually followed by a cross-case analysis. The institutional perspectives complement the strategic perspectives to provide a more complete analysis of environmental management. The cases illustrate that environmental management in these manufacturing firms can be leveraged for competitive advantage through innovation and cost savings in particular. However, the converse that innovation or other business requirements will be leveraged for environmental management, only sometimes applies even where a formal EMS is in place. Nevertheless, the prominence of environmental management is clearly linked to formalisation and to corporate policy and values. While environmental management is often aligned to quality and quality systems, environmental considerations are often subordinate to quality imperatives. The ability to link environmental management to business requirements such as cost savings and customer priorities is an effective way of achieving environmental improvements. Both regulations and individuals influence the direction and choice of many initiatives. A model is developed to enable a comprehensive understanding of the complexities of environmental management strategy and implementation in organisations. an open system of activities and influences. In the broader context, innovation systems and production capability triad are possible models for sustainable development.
Keywords: Business Studies, Ph.D.; Ph.D. Trinity College Dublin